Description of a new species of Leiopathes (Antipatharia: Leiopathidae) from the Hawaiian Islands - Wagner, Daniel; Opresko, Dennis M. (Zootaxa, 2015)
The Hawaiian antipatharian coral previously identified as Leiopathes glaberrima (Esper, 1792) and Leiopathes sp. is described using polyp morphology, skeletal spine morphology and in situ photographs, and assigned the new name of Leiopathes annosa sp. nov. The species is characterized by tall (1 m or more), fan-shaped colonies, with thick, sometimes overlapping branches, and tissues that are colored bright orange when alive. Skeletal spines are smooth, hemispherical, often times multi-lobed, and typically 75 μm tall, but range between 30–225 μm. Polyps are of variable size (0.88–3.35 mm) and arranged on all sides of the corallum on thicker branches, and uniserially on terminal branches. Leiopathes annosa sp. nov differs from all other nominal species of Leiopathes by having a generally flabellate corallum with thick branches and conspicuous skeletal spines that are multi-lobed and hemispherical. The biogeographical distribution of species within the monogeneric family Leiopathidae is presented and discussed.